CONCEPTUAL DIMENSIONS OF ELECTRONIC GOVERNMENT AND ELECTRONIC GOVERNANCE IN THE DOMAIN OF DIGITAL DEMOCRACY (International Journal of Innovative Technologies in Economy, 2022)
Further development of the domain of electronic (digital) democracy, which represents the result of implementation of electronic government and electronic governance, and implies the smart use of digital tools, substantially depends on how correctly is defined their conceptual dimensions and determined their functional purposes. E-government and E-governance (as terms and concepts), known as multidimensional, multifaceted and multidisciplinary phenomenon, are often treated as synonymous and used interchangeably in the academic literature or formal documents. Therefore it is becoming increasingly difficult to set a common definition (Roy, 2003) or clear existing conceptual ambiguity between them. There is no universally accepted definition of both abstractions. Such conceptual uncertainty has a negative impact on the development of digital democracy. The research objective of this article is to provide a deeper understanding of e-government and e-governance concepts through empirical studies and scatter the existing ambiguity in differences between these two concepts as this variety is not just questions of academic nuance. Based on a comparative analysis of e-government and e-governance definitions and conceptual meanings, this article offers an approach according to which e-government and e-governance represents two various but closely related and co-existing concepts. Furthermore, in the concluding section of the article, there are suggested recommendations regarding development a new grand term or concept in which both multidimensional conceptual visions will be combined.